A Clinical Comparative Study of Vishyandan Taila and Kashisadi Taila in Management of Bhagandara - Goud, Akshay Dinesh; Raja, MDP; Pachchinavar, KH; Yakkundi, RC; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2024)
Background: Anal fistula a common problem that causes substantial morbidity in persons who are otherwise healthy. It is one in which patient experiences pain, discharge and discomfort etc. This study was conducted to evaluate the effectiveness of Vishyandan taila with Kashisadi Taila as the management of Bhagandara (Fistula- in-ano). Objectives: The present clinical study aims to ascertain the effect of Vishyandan taila with Kashisadi Taila in management of Bhagandara. Methods: This study was conducted within the facilities the patients attending the O.P.D. and I.P.D. of Shalya tantra department of the S.S.R.A.M.C. Hospital, Inchal Bailahongal have been selected irrespective of their sex, religion, race, occupation etc. The total 40 patients presenting the features of Bhaganadara were selected randomly treated with a Vishyandan taila with Kashisadi Taila for duration of 14 days. Results: The treatment modalities of Vishyandan taila with Kashisadi Taila equally significant in management of Bhaganadara. Conclusion: It can be concluded that Vishyandan taila with Kashisadi Taila is significant in the management of Bhangandara.